The Effect of Zigzag Drills on the Dribbling Skills of Female Futsal Players at State High School 7 in South Bengkulu - Sinria Oktama Putri; Dolly Apriansyah; Roni Syaputra (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of Zig Zag training on the dribbling skills of female futsal players at SMA Negeri 7 South Bengkulu. The study used preexperimental research design using One-Group Pretest–Posttest Design. The research sample consisted of 17 female futsal players, selected using the total sampling technique. Data were collected through dribbling skills tests administered before and after the training program. The data were analyzed using descriptive statistics and the paired-samples t-test. The results indicated that Zig Zag training had a positive and statistically significant effect on the dribbling skills of the female futsal players. The statistical analysis revealed that the calculated t-count (3.027) exceeded the critical t-table (1.734) at a significance level of α = 0.05, indicating a significant improvement in dribbling skills following the training program. In conclusion, Zig Zag training is an effective training method for improving the dribbling skills of female futsal players at SMA Negeri 7 South Bengkulu.